Epidemiological profile and transmission dynamics of COVID-19 in the Philippines - Haw, Nel Jason L (Archīum Ateneo, 2020)
The Philippines confirmed local transmission of COVID-19 on 7 March 2020. We described the characteristics and epidemiological time-to-event distributions for laboratory-confirmed cases in the Philippines recorded up to 29 April 2020 and followed until 22 May 2020. The median age of 8212 cases was 46 years (IQR 32–61), with 46.2% being female and 68.8% living in the National Capital Region. Health care workers represented 24.7% of all detected infections. Mean length of hospitalisation for those who were discharged or died were 16.00 days (95% CI 15.48–16.54) and 7.27 days (95% CI 6.59–8.24). Mean duration of illness was 26.66 days (95% CI 26.06–27.28) and 12.61 days (95% CI 11.88–13.37) for those who recovered or died. Mean serial interval was 6.90 days (95% CI 5.81–8.41). Epidemic doubling time prior to the enhanced community quarantine (ECQ; 11 February and 19 March) was 4.86 days (95% CI 4.67–5.07) and the reproductive number was 2.41 (95% CI 2.33–2.48). During the ECQ (20 March to 9 April), doubling time was 12.97 days (95% CI 12.57–13.39) and the reproductive number was 0.89 (95% CI 0.78–1.02).